AKTIVITAS ANTIOKSIDAN PADA ENAM JENIS TUMBUHAN STERCULIACEAE - Saefudin; Sofnie Marusin; Chairul (Jurnal Penelitian Hasil Hutan, 2013)
Plants of Sterculiascas buve long been and at traditional medicines. Nine extracts of leaf, bark, and nuts of six Sterculiacnat species were evulnated for their antincidunt activity. Antioxidant activities were determined in vitro by free radical scavenging assay atay using 2.2-diphenyl-1-picrylhydrazyl (DPPH) radical Asorbic acid was wond at control. Among the 9 methanel otrasti testid, & showed antiradical DPPH attisties more than 50%, though still lower than the auerbic acid. Material extracted from bark showed the bigbest activity, in which the extract of Prerospermum javanicum's burk proudnod the highest antccidant activity (92.02), Plytubemical screening on three antacidant compted an arcation intees the high antecidant activities and the polyphenol compounds contained of the plant. Parts of plants that contain medio to many polyphenols, generally bare antisocidant actly abate 80 %.